Penerapan Metode EOQ dan JIT Dalam Pengendalian Persediaan Bahan Baku Pada Jasa UMKM Yuli Laundry - Khrisna, Khrisna Anggun Yuliana (PT. Karya Inovatif Nusantara, 2024)
One of the problems that laundry entrepreneurs cannot avoid is the inefficient use of washing materials and equipment, causing them to run out quickly. Yuli Laundry has not used the EOQ method in running a business and still uses the manual method by recording the required inventory raw materials. Based on these problems, the researcher is interested in conducting a study entitled “Application of EOQ and JIT Methods in Raw Material Inventory Control at Umkm Yuli Laundry Services”. This research was conducted with the aim of knowing the inventory control of Laundry raw materials and to find out the comparison between the total inventory of Laundry raw materials using the Yuli Laundry policy using the EOQ and JIT methods. The data is in the form of field observations and interviews that provide information both in writing and orally regarding the calculation of the production costs of UMKM Yuli Laundry. The Economic Order Quantity (EOQ) method results in a cost of Rp 614,500 for detergent raw materials, with savings of 83.1%. While the Just In Time (JIT) method resulted in a cost of Rp 1,267,547.36 with a production cost savings of 65.4%. After comparing inventory costs between the company, EOQ, and JIT methods, the authors recommend choosing the EOQ method because the total inventory cost of Rp 614,500 is lower than the company and JIT methods.